2020
DOI: 10.1002/hpm.3051
|View full text |Cite
|
Sign up to set email alerts
|

Is it worth outsourcing essential public health services in China?—Evidence from Beilin District of Xi'an

Abstract: Background: Essential public health services (EPHS) is general welfare public health interventions led by the Chinese government and provided by the primary medical institutions to all residents. In Beilin District, Xi'an, EPHS producers can be divided into outsourced institutions and public institutions. Objective: Can outsourcing EPHS reduce costs and improve efficiency and quality? There is still no definite answer to this question. This paper compares the performance of outsourced institutions and public i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…A recent study found that outsourced services including non-clinical services performed worse in quality than the public health services [ 28 ], findings consistent with our observation that outsourced Site 3 had a longer length of stay to achieve a likely decrease in functional independence, compared with the internally managed site. They explained their findings by the restraints in budget from the government that prioritizes cost reduction over quality of care.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A recent study found that outsourced services including non-clinical services performed worse in quality than the public health services [ 28 ], findings consistent with our observation that outsourced Site 3 had a longer length of stay to achieve a likely decrease in functional independence, compared with the internally managed site. They explained their findings by the restraints in budget from the government that prioritizes cost reduction over quality of care.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies of outsourcing have included non-clinical services such as business and IT support, plus clinical support services, such as laboratory services. In addition, our study adds to the literature by providing empirical data in the Australian health-care setting, where much of the available evidence on outsourcing is from countries with different health-care systems such as China [ 28 ] and the UK [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study explained that the reason for inequality in public health services, and the inefficiency of the fiscal transfer payment system, was Chinese local officials' fanatical pursuit of local economic growth in the vast majority of provinces (32). A study concluded that outsourced institutions provided by the primary medical institutions performed worse than public institutions led by the Chinese government in terms of efficiency and quality (33). In fact, despite developed cities such as Zhuhai, a cross-sectional study found government funds for basic public health services could not compensate for the actual costs under the constraints of a limited budget (34).…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, some scholars have deepened their understanding of public health services from one or more theoretical perspectives. Based on the “tripartite subject” framework, Yuan et al ( 14 ) discussed the differences in quality and production efficiency between public institutions and outsourced institutions. According to adverse selection and moral hazard in principal-agent theory, Zhang and Xu ( 6 ) designed incentive contract models to relieve asymmetric information problems in government procurement of public services.…”
Section: Literature Reviewmentioning
confidence: 99%